The impact of training programs, employee benefits and employee relations on job satisfaction : A case study of oil & gas company in Kuala Lumpur Malaysia - Anis Rina, Rosly (2024)
In this research, the training programmes, employee benefits, and workplace relations that relate to job satisfaction among oil and gas employees in Kuala Lumpur, Malaysia's oil and gas sector, have been evaluated. The study will examine how these three factors relate to worker satisfaction in a high-stress, high-demand industry. A quantitative methodology used questionnaires sent out to oil and gas employees, asking them to rate the training program, company benefits, and workplace relationships. The population in this study is 1400 employees, and the sample size after minus error of 5%, has been examined for 300 sample size results. The results based on the questionnaire were distributed online. The results should show that effective training, employee benefits and employee relations positively correlate with job satisfaction. This research reveals the realities of human resource management in oil and gas and recommends better employee retention, motivation and organisational effectiveness at oil and gas company